Reducing turbulent transport in tokamaks by combining intrinsic rotation and the low momentum diffusivity regime - Haomin Sun; Justin Ball; Stephan Brunner; Anthony Field; Bhavin Patel; Daniel Kennedy; Colin Roach; Diego Jose Cruz-Zabala; Fernando Puentes Del Pozo; Eleonora Viezzer; Manuel Garcia Munoz (Nuclear Fusion)
Based on the analysis of a large number of high-fidelity nonlinear gyrokinetic simulations, we propose a novel strategy to improve confinement in spherical tokamak plasmas by combining up-down asymmetric flux surface shaping with the Low Momentum Diffusivity (LMD) regime. We show that the intrinsic momentum flux driven by up-down asymmetry creates strong flow shear in the LMD regime that can significantly reduce energy transport, increasing the critical gradient by up to 25%. In contrast to traditional methods for generating flow shear, such as neutral beam injection, this approach requires no external momentum source and is expected to scale well to large fusion devices. The experimental applicability of this strategy in spherical tokamaks is addressed via simulations by considering actual equilibria from Mega Ampere Spherical Tokamak and a preliminary equilibrium from SMART.